Vaccination of human participants with attenuated Necator americanus hookworm larvae and human challenge in Australia: a dose-finding study and randomised, placebo-controlled, phase 1 trial. Issue 12 (December 2021) - Chapman, Paul R; Webster, Rebecca; Giacomin, Paul; Llewellyn, Stacey; Becker, Luke; Pearson, Mark S; De Labastida Rivera, Fabian; O'Rourke, Peter; Engwerda, Christian R; Loukas, Alex; McCarthy, James S
Summary: Background: Control of human hookworm infection would be greatly aided by the development of an effective vaccine. We aimed to develop a live attenuated human hookworm vaccine. Methods: This was a two-part clinical trial done at Q-Pharm in Brisbane (QLD, Australia) using a live ultraviolet C (UVC)-attenuated Necator americanus larvae vaccine. Part one was an open-label, dose-finding study using 50 L3 larvae suspended in water to a volume of 200 μL, attenuated with UVC exposure of 700 μJ (L3–700) or 1000 μJ (L3–1000). Part two was a randomised, double-blind, placebo-controlled, challenge study, in which participants were randomly assigned 2:1 to the vaccine group or placebo group. Healthy hookworm-naive adults aged 18–65 years with body-mass index 18–35 kg/m 2 received two doses of either placebo (Tabasco sauce) or vaccine (50 L3–700) on day 1 and day 42, followed by challenge with 30 unattenuated L3 larvae to both groups. All participants received a single oral dose of 400 mg albendazole 4 weeks after each inoculation and a 3-day course (400 mg orally daily) initiated on day 161 after the challenge phase, to eliminate any remaining infection. The primary outcome of part 1 was the level of larval attenuation the resulted in a grade 2 or 3 dermal adverse event. The primary outcome of part 2 was safety and tolerability, assessed by frequency and severity of adverse events in all randomly assigned participants. Prespecified exploratory outcomes in the challenge study were faecal N americanus DNA concentration, the number of N americanus larvae recovered per g of faeces cultured, hookworm antigen-specific serum IgG antibody responses, and hookworm antigen-specific peripheral blood cytokine responses. The trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12617001007325). Findings: Between Sept 19, 2017, and Oct 24, 2018, seven participants were enrolled into three cohorts in part one (two participants in cohort 1, who received L3-700; two participants in cohort 2, who received L3-700; and three participants in cohort 3, who received L3-1000) and a further 15 were enrolled into part two. There were no serious adverse events in part one or part two. In part one, a greater number of skin penetration sites were observed after administration of L3-700 than L3-1000 (mean 15·75 [95% CI 11·18 to 20·32] with L3-700 vs 4·33 [–1·40 to 10·07] with L3-1000). Similarly, greater erythema (median 225 mm 2 [IQR 150 to 325] vs 25 mm 2 [12·5 to 80]) and a longer duration of the dermal reaction (median 8·0 days [IQR 3·5 to 11·5] vs 2·0 days [2·0 to 4·5]) were observed after L3-700 than L3-1000. The mean number of adverse events per participant did not differ between the groups (3·25 [95% CI 1·48 to 5·02] vs 3·00 [1·04 to 4·96]). Thus, L3-700 was used for vaccination in part two. In part two, ten participants were randomly assigned to receive L3-700 and five to placebo. Significantly more adverse events occurred after vaccination with attenuated larvae than with placebo (incident rate ratio [IRR] 2·13 [95% CI 2·09 to 5·51]; p=0·0030). There was no difference between groups in the frequency of adverse events after challenge (IRR 1·25 [0·78 to 2·01]; p=0·36). Most adverse events were mild in severity, with only one severe adverse event reported (erythematous and indurated pruritic rash >100 mm in a vaccine group participant after challenge). The eosinophil count increased in all participants after challenge, with a significantly greater increase among vaccinated participants than placebo participants (1·55 × 10 9 cells per L [IQR 0·92 to 1·81] in the vaccine group vs 0·49 × 10 9 cells per L [0·43 to 0·63] in the placebo group; p=0·014). Vaccinated participants had an IgG response to larval extract after challenge that was higher than that in placebo participants (increase in IgG titre 0·22 [IQR 0·10 to 0·41] vs 0·03 [–0·40 to 0·06]; p=0·020). Significantly fewer larvae per g of faeces were recovered in the vaccine group than in the placebo group after challenge (median larvae per g 0·8 [IQR 0·00 to 3·91] vs 10·2 [5·1 to 18·1]; p=0·014). The concentration of N americanus DNA in faeces was not significantly different between the vaccinated group and the placebo group (log10 DNA intensity 4·28 [95% CI 3·92 to 4·63] vs 4·88 [4·31 to 5·46]; p=0·14). Peripheral blood mononuclear cells from vaccinated participants exhibited significantly greater cytokine production at day 112 than placebo participants for IFNγ, TNFα, IL-2, IL-4, and IL-5 (p<0·05), but not IL-10. Interpretation: Vaccination with UVC-attenuated N americanus larvae is well tolerated, induces humoral and cellular responses to hookworm antigens, and reduces larval output after challenge with unattenuated larvae. Larger studies are required to confirm protective efficacy. Funding: National Health and Medical Research Council of Australia.